CRITERIA FOR DIAGNOSIS OF ISTHMYCERVICAL INSUFFICIENCY IN MULTIPLE PREGNANCY. CORRECTION METHODS - Kayumova G.M. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
According to most researchers dealing with the problem of multiple pregnancies, extreme prematurity occupies a leading place among the causes of high perinatal losses and severe neurological diseases in twins [1, 2, 3, 4]. The frequency of premature births in multiple pregnancy, according to the literature, ranges from 30 to 65% [5, 6]. According to M. Gardner et al . [5], in the structure of the causes of premature birth in multiple pregnancy, 22% belongs to premature rupture of amniotic fluid. In most cases, the opening of the amniotic sac occurs against the background of premature shortening of the cervical canal and opening of the internal pharynx. According to B. Arabin et al ., the cause of the formation of isthmic -cervical insufficiency (ICI) in multiple pregnancy is overextension of the isthmus region against the background of accelerated growth of the uterine cavity [7]. To form a risk group for premature birth in multiple pregnancies, transvaginal ultrasound examination of the cervix, performed in the middle of the second trimester of pregnancy (23-25 weeks), is generally accepted, which makes it possible to develop and apply obstetric tactics aimed at prolonging pregnancy in the form of drug correction and creating therapeutic protective regime [8, 9]. However, it should be noted that the need to take medications and a significant limitation of physical activity make a certain unfavorable contribution to the psycho- emotional sphere of a pregnant woman and do not have a guaranteed therapeutic effect [10, 11]. Materials and methods. As an experimental group, we examined 61 women with twin pregnancies without clinical signs of threatened miscarriage.